KANDUNGAN TIMAH HITAM ( PLUMBUM) PADA TANAMAN PENEDUH JALAN DI KOTA DENPASAR - Juni Antari, A.A Raka; Sundra, I Ketut (Bumi Lestari, 2012)
This study was aimed to observe the content of led substances (Pb) in Angsana,s (Pterocarpus indicus Willd) and Glodogan,s (Polyalthia longifolia Bent & Hook. F ) leaves growing along the busy roads in Denpasar. The study was conducted from November to December 2002. Sample were obtained from five location with busy traffics while another one was from un busy traffics as control. Sample were analysed at Analytic Laboratory, Udayana University using wet digestion method, then were analysed using Atomic Absorbance Spectrofotometer (AAS). Result showed that the lead (Pb) content in Angsana’s leave out weighed the Glodogan’s leave and Pb content on November exceeded that on December 2002. Overall, analysis of all samples, on November and December 2002, indicated that the Pb content was bellow the standard allowed which was 1000 ppm (?g/g)
Keywords: lead, angsana, glodogan.